Privacidade de dados em Blockchain: um estudo sobre a conformidade regulatória com as regulamentações de proteção de dados do Brasil e da Europa - Farias Júnior, Tácito Augusto (2024)
Data privacy refers to the fundamental right of individuals to control their personal information and the way that information is collected, stored and used. This covers protecting data against leaks and unauthorized access. In this context, regulations such as the General Data Protection Law (LGPD) in Brazil and the General Data Protection Regulation (GDPR) in Europe were developed to manage privacy and the processing of personal data. Blockchain, an emerging technology that uses a Blockchain to record transactions in an immutable, decentralized and transparent manner, presents compliance challenges with these data protection regulations. This dissertation presents as its main objective an analysis of the data privacy regulatory compliance existing in Blockchain with the LGPD and GDPR. The methodology of this work consists of a Systematic Literature Mapping (MLS) that investigates Blockchain’s regulatory compliance with the LGPD or GDPR in relation to data privacy. Subsequently, a comparative study is carried out between 2 (two) of the main encryption and privacy techniques used in Blockchain, Zero-Knowledge Proof (ZKP) and Ring Signatures, aiming for regulatory compliance with the LGPD and GDPR. Ultimately, this dissertation contributes to the understanding of data privacy issues in Blockchain and provides insights for companies, organizations and regulators on the use of Blockchain technology in regulatory compliance with data protection regulations from Brazil and Europe.